A review of longnose skates Zearaja chilensis and Dipturus trachyderma (Rajiformes: Rajidae) (Universitas Scientiarum, 2015)
Longnose skates may have a high intrinsic vulnerability among fishes due to their large body size, slow growth rates and relatively low fecundity, and their exploitation as fisheries target species places their populations under considerable pressure. They are found circumglobally in subtropical and temperate coastal waters. Although longnose skates have been recorded for over 150 years in South America, the ability to assess the status of these species is still compromised by critical knowledge gaps. Based on a review of 185 publications, a comparative synthesis of the biology and ecology was conducted on two of the most commercially important elasmobranchs in South American waters, the yellownose skate Zearaja chilensis and the roughskin skate Dipturus trachyderma; in order to examine and compare their taxonomy, distribution, fisheries, feeding habitats, reproduction, growth and longevity. There has been a marked increase in the number of published studies for both species since 2000, and especially after 2005, although some research topics remain poorly understood. Considering the external morphological similarities of longnose skates, especially when juvenile, and the potential niche overlap in both depth and latitude occupied, it is recommended that reproductive seasonality, population structure and connectivity be assessed to ensure their long-term sustainability.